Pseudoepitheliomatous keratotic and micaceous balanitis: a rare interesting case report - Damodaran, Devi; Rajagopalan, Rajesh; Vethanayagam, Mohankumar; Kandasamy, Revathi (International Journal of Research in Dermatology, 2024)
Pseudoepitheliomatous micaceous balanitis (PEKMB) is an uncommon non-venereal dermatosis primarily affecting males. PEKMB typically affects individuals above 50 years of age, with circumcision being a potential predisposer. Here, we report a case of a middle-aged male who was referred from the surgery department with genital lesions persisting even with treatment for 6 months. Clinical examination revealed hypopigmented to erythematous lesions with scaling over the glans penis, accompanied by urethral meatus narrowing. Despite conservative treatments on his own and with general practitioners, there was no improvement. Histopathological examination confirmed the features of PEKMB without malignancy. Treatment with topical emollients/ 5% 5 fluorouracil was initiated. Differential diagnoses include psoriasis, circinate balanitis, and malignant squamous epithelioma. Treatment options include topical steroids, 5% 5-fluorouracil cream, photodynamic therapy (PDT), etc. This case highlights the rarity of PEKMB and underscores the importance of early diagnosis and long-term follow-up.